2012
DOI: 10.1016/j.mayocp.2012.02.010
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Fibromyalgia Management for Primary Care Providers

Abstract: Fibromyalgia is a chronic widespread pain disorder commonly associated with comorbid symptoms, including fatigue and nonrestorative sleep. As in the management of other chronic medical disorders, the approach for fibromyalgia management follows core principles of comprehensive assessment, education, goal setting, multimodal treatment including pharmacological (eg, pregabalin, duloxetine, milnacipran) and nonpharmacological therapies (eg, physical activity, behavioral therapy, sleep hygiene, education), and reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
103
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(127 citation statements)
references
References 40 publications
(61 reference statements)
3
103
0
3
Order By: Relevance
“…The severity of depressive symptoms in the group of positive patients was distributed as mild level of depression in 54.9% of detected cases and 45.1% of major depression (Figures 6 and 7). These indings are consistent with the results of a number of authors, according to which the depressive disorders were observed in approximately 90% of patients with FM and major depression was established in 62-86% of cases [12,[19][20][21][22].…”
Section: Depressive Symptomssupporting
confidence: 92%
“…The severity of depressive symptoms in the group of positive patients was distributed as mild level of depression in 54.9% of detected cases and 45.1% of major depression (Figures 6 and 7). These indings are consistent with the results of a number of authors, according to which the depressive disorders were observed in approximately 90% of patients with FM and major depression was established in 62-86% of cases [12,[19][20][21][22].…”
Section: Depressive Symptomssupporting
confidence: 92%
“…The current treatment for FM envisages a comprehensive assessment including pharmacological and non-pharmacological therapies. The latter provide for a multimodal approach including physical activity, sleep hygiene, behavioural therapy, regular education and monitoring of treatment response [14,15] . It has been shown that regular exercise, in particular aerobic, improves pain, fatigue and sleep disturbance in patients with FM.…”
Section: Rheumatic Diseasesmentioning
confidence: 99%
“…Ос-новные побочные эффекты -головокружение, сонливость, сухость во рту, нечеткость зрения [42] -выражены слабо, отмечаются в начале терапии и проходят самостоятельно при ее продолжении. У некоторых пациентов наблюдается увеличение массы тела (дозозависимый эффект).…”
Section: д и а г н о с т и ч е с к и е к р и т е р и и ф м 2 0 1 0 г unclassified